Estrategias De Afrontamiento Y Percepción De La Calidad De Vida En Personas Con Vih Perternencientes A La Fundación Eudes (2018)
A case study was carried out with a descriptive method with the aim of analyzing the strategies of coping and perception of quality of life present in people with HIV positive of the Eudes foundation. An inventory was applied for Quality of Life called WHOQOL BREF and an inventory for CSI coping strategies, in addition to a semi-structured interview, where behavioral cognitive aspects are explored against the disease.